Monitoring Minimal Residual Disease in the Myeloproliferative Neoplasms: Current Applications and Emerging Approaches. (20th October 2016) - Haslam, Karl; Langabeer, Stephen E.
Abstract : The presence of acquired mutations within the JAK2, CALR, and MPL genes in the majority of patients with myeloproliferative neoplasms (MPN) affords the opportunity to utilise these mutations as markers of minimal residual disease (MRD). Reduction of the mutated allele burden has been reported in response to a number of therapeutic modalities including interferon, JAK inhibitors, and allogeneic stem cell transplantation; novel therapies in development will also require assessment of efficacy. Real-time quantitative PCR has been widely adopted for recurrent point mutations with assays demonstrating the specificity, sensitivity, and reproducibility required for clinical utility. More recently, approaches such as digital PCR have demonstrated comparable, if not improved, assay characteristics and are likely to play an increasing role in MRD monitoring. While next-generation sequencing is increasingly valuable as a tool for diagnosis of MPN, its role in the assessment of MRD requires further evaluation.